Determination of production capacity for open-pit coal mines under uncertainty: A model based on economies of scale. - Shuai Wang; Bo Cao; Runcai Bai; Guangwei Liu (PLoS ONE)
The determination of optimal production capacity for open-pit mines is influenced by various economic and technical factors and is highly susceptible to uncertainties. To effectively address the impact of uncertainty on capacity planning, this study develops a production capacity planning model for open-pit coal mines, based on the theory of economies of scale and incorporating multiple uncertainty constraints. A novel method is proposed to quantify and propagate the uncertainties of key capacity control factors, alongside a comprehensive uncertainty analysis framework for total revenue. Using a large-scale open-pit mine as a case study, the relationships and calculation tables for the uncertainties of key control factors are provided. Based on this, a mathematical expression for total revenue under the influence of multiple uncertainties is formulated, and the optimal capacity range is calculated. The application of the model is demonstrated through this case study, revealing that the uncertainties in production costs and coal prices are (-13.05%, +27.68%) and (-10.79%, +10.79%) respectively. Subsequently, risk-tolerant capacity planning recommendations are proposed, effectively mitigating the impact of uncertainties on production capacity determination.